Preparation and characterization of superhydrophilic nanocomposite ultrafiltration membranes for treatment of highly concentrated oil-in-water emulsion - Lai, Gwo Sung (Penerbit UTM Press, 2017)
In oily wastewater treatment using membrane technology, surface fouling is the major issue that could deteriorate membrane flux and shorten its lifespan. Therefore, nanocomposite membranes were developed in this study by incorporating titanium dioxide (TiO2) and hydrous manganese oxide (HMO) nanoparticles into polymeric membrane matrix. Three different types of membranes were fabricated. They were pristine PES and membrane incorporated with TiO2 or HMO. With respect to pure water flux, TiO2- and HMO-incorporated membranes showed value of 57 and 40 L/m2.h, respectively. These values were 33-90% higher than that of control PES membrane. In treating 500 ppm oily solution, TiO2 membrane exhibited the highest water flux. However, the membrane’s oil removal rate was slightly compromised. When tested with higher concentration of oily solution (5,000 or 10,000 ppm), TiO2- and HMO-incorporated membranes still showed promising water flux with 94.5-99.6% oil removal rate. This proved that ultrafiltration membrane incorporated with suitable nanomaterials could improve the water flux of pristine PES membrane and is of more practical for industrial applications.